The incidence and prognostic effect of Fms-like tyrosine kinase 3 gene internal tandem and nucleolar phosphoprotein 1 genes in acute myeloid leukaemia: A PRISMA-compliant systematic review and meta-analysis. Issue 51 (18th December 2020) - Liu, Heping; Zhang, Xiaolian; Li, Ming; Zhou, Wei; Jiang, Guangrong; Yin, Weihua; Song, Chunping
Abstract: Background: Molecular genotyping is an important prognostic role in acute myeloid leukemia (AML) patients. We aimed to design this meta-analysis to discuss the incidence and prognostic effect of nucleolar phosphoprotein 1 (NPM1) and Fms-like tyrosine kinase 3 gene internal tandem (FLT3-ITD) gene in AML patients. Methods: PubMed, Embase, Medline, and Cochrane library were systematically searched due to May 15, 2020. Four combinations of genotypes (FLT3-ITD neg /NPM1 mut, FLT3-ITD pos /NPM1 mut, FLT3-ITD neg /NPM1 wt, FLT3-ITD pos /NPM1 wt ) were compared in association with the overall survival (OS) and leukemia-free survival (LFS) outcome, which expressed as pooled hazard ratio (HR) and 95% confidence intervals (CIs). Results: Twenty-eight studies were included in our study. The incidence of FLT3-ITD neg /NPM1 mut, FLT3-ITD pos /NPM1 mut, FLT3-ITD neg /NPM1 wt, and FLT3-ITD pos /NPM1 wt was 16%, 13%, 50%, and 10%, respectively. The patients with FLT3-ITD neg /NPM1 mut gene may have the best OS and LFS when comparing with FLT3-ITD pos /NPM1 mut (HR = 1.94 and 1.70, P < .01), FLT3-ITD neg /NPM1 wt (HR = 1.57 and 2.09, P < .01), and FLT3-ITD pos /NPM1 wt (HR = 2.25 and 2.84, P < .001). Conclusion: AML patients with FLT3-ITD neg /NPM1 mut gene type have the best survival outcome than the other 3 gene types, which should be an independent genotyping in AML classification.